2014
DOI: 10.1186/1756-3305-7-429
|View full text |Cite
|
Sign up to set email alerts
|

Dog-walking behaviours affect gastrointestinal parasitism in park-attending dogs

Abstract: BackgroundIn urban parks, dogs, wildlife and humans can be sympatric, introducing the potential for inter- and intra-specific transmission of pathogens among hosts. This study was conducted to determine the prevalence of zoonotic and non-zoonotic gastrointestinal parasites in dogs in Calgary city parks, and assess if dog-walking behaviour, park management, history of veterinary care, and dog demographics were associated with parasitism in dogsMethodsFrom June to September 2010, 645 questionnaires were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 41 publications
(56 reference statements)
5
54
3
Order By: Relevance
“…in PA dogs is less than reported within a previous year and similar geographical area [16]. Although sample collection design differed between the past and present studies, there may be a minor underestimate in overall prevalence in the current study due to operator bias, presuming the senior operator is more adept at preparing samples for microscopy.…”
Section: ·720 <0·001contrasting
confidence: 67%
See 2 more Smart Citations
“…in PA dogs is less than reported within a previous year and similar geographical area [16]. Although sample collection design differed between the past and present studies, there may be a minor underestimate in overall prevalence in the current study due to operator bias, presuming the senior operator is more adept at preparing samples for microscopy.…”
Section: ·720 <0·001contrasting
confidence: 67%
“…Within the social sciences, investigations into the relationships between spatial and temporal patterns of dog-walking, dog-to-dog contact, and dog demographics have indirectly explored behaviours that could influence the risk of GI disease transmission in dogs [3,[11][12][13]. However, only a limited number of studies have investigated the extent to which parks might pose risks for infection and transmission of GI parasites in dogs [2,7,9,[13][14][15][16][17][18][19][20][21], a relevant query given that in urban settings, parks figure prominently as dog-walking destinations [22]. Giardia spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies 80,82,83 have revealed an increased risk of enteric infection (ie, Giardia spp, Campylobacter spp, or Cryptosporidium spp) for unleashed dogs at dog parks, compared with the risk for leashed dogs; increased exposure to canine feces is likely one of the factors contributing to this increased risk.…”
Section: Enteric Disease Preventionmentioning
confidence: 99%
“…Previously, we examined dog-walking behavior within parks with different leashing regulations (hereafter 'park management'), including off-leash areas, on-leash areas, and parks with both off-leash and on-leash areas (hereafter, 'mixed-managed parks'), and found a significant positive association between GI parasitism and certain recreational behaviors, including off-leash frequency (Smith et al, 2014). And on a broader scale, Westgarth et al (2009) investigated connectivity among dogs and owners in neighboring communities and established a high potential for contact through use of communal areas including parks, supporting the potential for parasite transmission both within and among parks.…”
Section: Introductionmentioning
confidence: 99%